Impact of spaceflight on gene expression in cultured human mesenchymal stem/stromal cells. - Peng Huang; Bryan T Piatkowski; Yesesri Cherukuri; Yan W Asmann; Abba C Zubair (PLoS ONE)
With technological advancements, human's desire to explore space is growing and more people are staying longer at the international space station (ISS). The impact of microgravity on stem cells (SC) is not fully understood. We explored the impact of microgravity on gene expression profile of cultured mesenchymal stem/stromal cells (MSCs) at the ISS. We also evaluated how the new knowledge gained sheds light on our understanding of human physiology on Earth. Primary cultures of MSCs were expanded at the ISS for 1 or 2 weeks and mRNA was isolated from samples of the cultured cells. Gene expression profiles were determined and compared with samples from real-time ground control cultures. Differential gene expression, gene set enrichment analysis and determination of key genes were performed that revealed for the first time the existence of potential "master regulators" coordinating a systemic response to microgravity. Cyclin D1 (CCND1), a protein-coding gene that regulates cell cycle progression and CDK kinases, was identified as the most connected regulator at week 1. Further analysis showed the impacted genes from cultured MSCs significantly correlated with known gene pathways associated with cell division, chromosomal segregation and nuclear division, extracellular matrix structure and organization, muscle apoptosis and differentiation. This study exemplifies the utility of space research to advance our understanding of human physiology both on Earth and in space.